Evaluation of bait attractiveness for forensically important flies in lowland and montane forest in peninsular Malaysia - Goh, T.G.; Chen, C.D.; Jeffery, J.; Izzul, A.A.; Lau, K.W.; Lee, H.L.; Ramli, R.; Nazni, W.A.; Sofian-Azirun, Mohd (2013)
Background: Blowflies (order: Diptera, family: Calliphoridae) and house flies (order: Diptera, family: Muscidae)are important indicators to determine postmortem intervals in forensic entomology. Knowledge of the ecology and bionomics of individual species is necessary for the use of these flies as forensic indicators. Baited trapping is often employed to collect flies for such studies. However, the effect of baits on the diversity and abundance of baited trap collections is not known.Objective: To compare the sampling effectiveness of several types of bait in terms of diversity and abundance of forensically important flies.Materials and methods: The effectiveness of belacan (fermented shrimp paste), sugar, beef, ox liver, and fish were tested in three locations at different altitudes in Malaysia; Gombak Field Study Station (about 200 m above sea level (a.s.l.); N3Ì19'28?, E101Ì45'09?), Awana (about 1100 m a.s.l.; N3Ì24'03? E101Ì46'59?) and Bukit Cincin (about 1700 m a.s.l.; N3Ì25'58? E101Ì47'05?).Results: Fish consistently attracted more flies and species than other baits. Beef and ox liver produced moderate or inconsistent results. Flies were rarely attracted to preserved baits such as shrimp paste or odorless baits such as sugar. At higher elevations, flies were attracted to a wider variety of baits. Meat may cause a bias towards mated gravid females and produce a biased sample of the true population.Conclusion: Fish produced the most consistent results in terms of highest number of flies collected and wide diversity of species sampled, odor, especially from rotting meat, is important in attracting carrion flies.